Prevalence of Dental Caries and Its Associated Factors among Primary School Children in Ethiopia - Anguach Shitie; Rahel Addis; Abebe Tilahun; Wassie Negash (International Journal of Dentistry)
Background. Dental caries (decay or cavities) is a breakdown of teeth as a result of bacteria. Dental caries is one of the preventable oral health problems and the most common chronic diseases in childhood. Poor dental and oral health affect the quality of children’s life. Objectives. To estimate the prevalence of dental caries and its associated factors among primary school children in Alem Ketema, North Showa, Ethiopia. Methodology. An institution-based quantitative cross-sectional study was conducted on 422 primary school children, from February 9 to March 8, 2020. Pretested structured questionnaire and oral examinations were conducted by using the WHO criteria (DMFT) index to collect the data. The data were entered into Epi-Data 3.1 software, and analysis was carried out using SPSS version 23 and variables with P value ≤0.05 in the multivariable binary logistic analysis were considered as a cut-point to declare statistical significance. Result. The prevalence of dental caries was 46.9% (95% CI: 42.1, 51.7). The mean Decayed, Missing, and Filled Teeth (DMFT) index was 1.28 (±1.21). Being male (AOR = 1.975, 95% CI = 1.067–3.66), lack of parents’ insistence (AOR = 2.052, 95% CI = 1.079–3.902), lack of oral health education program (AOR = 4.753, 95% CI = 1.69–13.38), history of dental aches (AOR = 2.88, 95% CI = 1.55–5.32), and poor habit of mouth wash (AOR = 4.74, 95% CI = 2.55–8.79) were found significantly associated with dental caries. Conclusion. The prevalence of dental caries was higher and a common public health problem among school children. Lack of parent’s insistence, sex, dental ache history, poor practices of mouth wash, and lack of oral health education were significant predictors of dental caries. Therefore, oral health education program and parents encouraging their children to practice oral hygiene are important to prevent dental caries.